Indoor thermal comfort comparison between healthy and older adults with chronic diseases in community senior centers - Zhonghai Wang; Meng Zhen; Yu Shao; Lei Li; Mengyao Xiao (Case Studies in Thermal Engineering, 2025)
Thermal comfort in indoor environments of community senior centers plays a critical role in the well-being of older adults. This study examines the impact of seasonal variation on thermal perception and explores differences across health conditions, activity levels, and age groups. Field meteorological monitoring and surveys were conducted at a senior center in Zhangjiakou, China, yielding 1,275 valid responses across four seasons. Operative temperature (Top) was used to define thermal benchmarks and analyze perception differences. Results show: (1) Clothing insulation among older adults significantly decreases with rising Top; (2) Neutral Top values of 22.2 °C in spring, 26.1 °C in summer, 22.0 °C in autumn, and 21.1 °C in winter, and an annual neutral Top of 21.9 °C, ranging from 14.5 °C to 29.4 °C; (3) Among participants with chronic respiratory diseases, the neutral Top was 21.3 °C, 2.1 °C higher than that of healthy individuals; (4) The neutral Top for older adults aged 80 and above was 20.9 °C, which was 1.8 °C and 1.5 °C higher than that of the 60–69 (19.1 °C) and 70–79 (19.4 °C) age groups, respectively; (5) The neutral Top for low-intensity activities (22.7 °C) is 3.6 °C higher than that for moderate-intensity activity (19.1 °C). Findings inform climate-responsive indoor design tailored to the thermal comfort needs of aging populations.